Enhancing Intercultural Competence Through Cross-Cultural Understanding Among Indonesian and Thai Students - Ajeng Dianing Kartika; Wisma Kurniawati; Meilita Hardika (ABISATYA : Journal of Community Engagement, 2026)
Intercultural competence has become an essential skill for students in the era of globalization and international academic collaboration. According to Deardorff (2020), intercultural competence refers to the ability to communicate effectively and appropriately in intercultural situations based on knowledge, skills, and attitudes. This community engagement program aimed to enhance intercultural competence through cross-cultural understanding among Indonesian and Thai students. The program involved 50 participants consisting of 25 students from Walailak University and 25 students from the German Literature Study Program at Universitas Negeri Surabaya. The activities were conducted through three main stages: intercultural understanding training, intercultural competence workshops, and focus group discussions addressing contemporary cultural issues in Asia and Europe. The training activities were initiated with a pre-test and concluded with a post-test to evaluate participants’ intercultural understanding improvement. The results indicated a significant increase in participants’ intercultural awareness, communication skills, and understanding of cultural diversity between Indonesia and Thailand. The findings suggest that intercultural engagement activities can effectively foster multicultural awareness and global competencies among university students.